Forest transformation effects on the soil water-holding capacity depend on the forest characteristics and soil properties: A case study in the subtropical regions of southeast China - Jiantao Zhou; Qiao Yang; Xin Peng; Qiqian Wu; Yan Peng; Yutong Zhang; Hualing Jiang; Fuzhong Wu; Kai Yue (Journal of Forest Science, 2025)
Forest transformation commonly occurs in subtropical areas due to extensive human disturbance. However, we know little about how forest transformation may affect the soil water-holding capacity. Here, we evaluated the effects of forest transformation from natural forests to secondary forests, Castanopsis carlesii plantations, and Cunninghamia lanceolata plantations on the soil water-holding capacity, including the soil water content (SWC), maximum water holding rate (Rt), capillary holding rate (Rc), and non-capillary water holding rate (Rn), and assessed the influences of soil properties and stand characteristics on the forest transformation effects. The results showed that (i) the soil water-holding capacity in secondary forests increased significantly (SWC: 27.3%; Rt: 50.9%; Rc: 36.9%; Rn: 14.0%), but decreased in the Cunninghamia lanceolata plantations (SWC: 24.6%; Rt: 47.0%; Rc: 34.0%; Rn: 13.0%), compared to the nature forests (SWC: 26.0%; Rt: 48.3%; Rc: 34.9%; Rn: 13.4%); (ii) the soil water-holding capacity was positively correlated with the soil porosity, soil total nitrogen concentration, stand density, but negatively influenced by the soil bulk density and diameter at breast height (DBH); and (iii) the stand density, DBH and litterfall amount were the major factors regulating the soil water-holding capacity after the forest transformation. Overall, these results indicated that the soil water-holding capacity would be strongly altered by the forest transformation, but it depends on the soil properties before the transformation and the characteristics of the transformed forests. Our findings will help to better understand the functions of forests in water source conservation under the pressures of human disturbances and environmental changes.